A study on the macroeconomic variables that influence Shariah Index: case of United Kingdom / Mohd Nur Ridhwan Musa - Musa, Mohd Nur Ridhwan (Faculty of Business and Management, 2011)
Shariah Index is an index that conclude the stocks of Shariah-compliant company. Therefore, company that listed in it should follow the Shariah law that is base on the Al-Quran and As- Sunnah. This research is conducted to discover the either there is any relation between Shariah index stock price with three selected macroeconomic variables selected which involve Interest rate, Inflation rate and also Currency plus to discover which of these three variables give the biggest impact toward the Shariah index stock price. Market selected is United Kingdom Shariah Index and the specific scope had choose S&P Europe 350 Shariah Index since the United Kingdom Shariah index included in this type of index. In the process of discovering the result in the research methodology chapter, Multiple Linear Regression model is selected and three year period in a monthly basis as the scope of research starting from April 2008 until March 2011. In the finding chapter, the result shown that there is no relationship between all those independent variables affecting the S&P Europe Shariah Index stock price even there are still a positive and negative relationship shows in the equation. In conclusion, the S&P Europe Shariah Index stock price is influence by the other macroeconomic variables that is not included in this research, variables like unemployment, gross domestic product, population etc. would be the macroeconomic variables that is recommended for the future research.